Trade Costs and Development : A New Data Set - Arvis, Jean-François; Shepherd, Ben; Duval, Yann; Utoktham, Chorthip (World Bank, Washington, DC, 2014)
The World Bank and the United Nations Economic and Social Commission for Asia and the Pacific (UNESCAP) jointly prepared a new global data set of bilateral trade costs based on trade and production data. Accessible on the World Bank Open Data Web site, it opens new analytical possibilities for policy makers and researchers working on trade integration. The data stress the importance of supply chains and connectivity constraints in explaining the higher costs and lower levels of trade integration observed in developing countries. To measure trade costs in the developing world over the 1995-2010 period, UNESCAP and the World Bank embarked on a joint data collection exercise. In addition to data on export and import flows, calculation of trade costs using the inverse gravity methodology also requires information on domestic production in each country. Usage can then be calculated as domestic production less total exports. The result of the data collection exercise is a database covering up to 178 countries, two sectors, and the 1995-2010 period. Based on the available data, trade costs data are calculated for as many bilateral pairs as possible, and interpolation used to fill in missing country- year combinations when feasible.